2005
DOI: 10.1152/ajpheart.00958.2004
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone treatment increases thromboxane function in rat cerebral arteries

Abstract: We previously showed that testosterone, administered in vivo, increases the tone of cerebral arteries. A possible underlying mechanism is increased vasoconstriction through the thromboxane A2 (TxA2) pathway. Therefore, we investigated the effect of chronic testosterone treatment (4 wk) on TxA2 synthase levels and the contribution of TxA2 to vascular tone in rat middle cerebral arteries (MCAs). Using immunofluorescence and confocal microscopy, we demonstrated that TxA2 synthase is present in MCA segments in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 45 publications
2
52
0
Order By: Relevance
“…Several studies have also shown that testosterone can cause vasodilation by acting via large conductance calcium-activated potassium channels (10,58,62). However, chronic testosterone supplementation has been shown to increase myogenic tone (13,18) and production of thromboxane A 2 , a potent vasoconstrictor in cerebral arteries (17). It is possible that enhanced estradiol in females and/or elevated testosterone in males contributes to the observed sex difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have also shown that testosterone can cause vasodilation by acting via large conductance calcium-activated potassium channels (10,58,62). However, chronic testosterone supplementation has been shown to increase myogenic tone (13,18) and production of thromboxane A 2 , a potent vasoconstrictor in cerebral arteries (17). It is possible that enhanced estradiol in females and/or elevated testosterone in males contributes to the observed sex difference.…”
Section: Discussionmentioning
confidence: 99%
“…Like estradiol, testosterone has been shown to effect vascular function. However, effects of testosterone on vascular function are not well defined, since testosterone has been reported to have both vasodilatory effects (8,10,14,24,40,58,62) and vasoconstrictor effects (13,17,18).…”
Section: Discussionmentioning
confidence: 99%
“…During DHT treatment, a difference was noted in Ach-relaxation. By blocking the NO pathway, minor contractions were detected, suggesting the local involvement of the prostanoid system (11,36) and muscarinic Ach receptors (37) in addition to the NO pathway. It has been shown that insulin-dependent relaxation of the large vessels (aorta) and gracilis arterioles are predominantly mediated by NO and endothelium-derived hyperpolarizing factor/potassium channels, respectively (38).…”
Section: Figurementioning
confidence: 99%
“…Gonadectomy and hormone treatment protocols were performed on three-month-old female and male Fischer 344 rats (Charles River-SASCO Laboratories; Wilmington, MA) as described previously (Geary et al, 2000;Gonzales et al, 2005;McNeill et al, 1999;Razmara et al, 2005). Female rats were divided into three groups: intact, ovariectomized (OVX), and OVX treated with 17β-estradiol (OVX+E).…”
Section: In Vivo Animal Hormone Treatmentsmentioning
confidence: 99%